How Documentary Remade Mike Tyson. (December 2017) - Fuhs, Kristen
This article will theorize the relationship between stardom and documentary by considering the ways in which documentary representations contribute to the discursive formation of a star. Specifically, the article will explore the central role that documentary film has played in remaking Mike Tyson's public image by analyzing the boxer's representation across three distinct films: Fallen Champ: The Untold Story of Mike Tyson (Barbara Kopple, 1993), Tyson (James Toback, 2008), and Mike Tyson: Undisputed Truth (Spike Lee, 2013).